2018
DOI: 10.1002/aenm.201702998
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Electrode Materials in Sodium‐Ion Batteries

Abstract: Sodium‐ion batteries have attracted extensive interest as a promising solution for large‐scale electrochemical energy storage, owing to their low cost, materials abundance, good reversibility, and decent energy density. For sodium‐ion batteries to achieve comparable performance to current lithium‐ion batteries, significant improvements are still required in cathode, anode, and electrolyte materials. Understanding the functioning and degradation mechanisms of the materials is essential. Computational techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 299 publications
(677 reference statements)
3
137
0
Order By: Relevance
“…To grasp more insights into these experimental findings, DFT calculations were performed to look at the relative stabilities and the corresponding electronic structures of the Na 3+ y V 2− y Mn y (PO 4 ) 3 phases ( Figure 5 ). The relative stabilization energies of the Na 3+ y V 2− y Mn y (PO 4 ) 3 systems have been ascertained from their formation energies with respect to varying Mn content ( y ) and V content (2‐ y ): leftΔEf= E[]normalNa3+yV2ynormalMnyfalse(normalPO4false)3 1 yE[]V2ynormalMnyfalse(normalPO4false)3 yE[]normalNa4normalVMnfalse(normalPO4false)3 It is important to mention here that all energies are calculated per formula unit of the species. The trend in the values of formation energies does not follow a typical convex hull in the compositional phase diagram; a break appears at y = 0.50, as indicated by a sharp shoot‐up in the formation energy value (Figure a).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…To grasp more insights into these experimental findings, DFT calculations were performed to look at the relative stabilities and the corresponding electronic structures of the Na 3+ y V 2− y Mn y (PO 4 ) 3 phases ( Figure 5 ). The relative stabilization energies of the Na 3+ y V 2− y Mn y (PO 4 ) 3 systems have been ascertained from their formation energies with respect to varying Mn content ( y ) and V content (2‐ y ): leftΔEf= E[]normalNa3+yV2ynormalMnyfalse(normalPO4false)3 1 yE[]V2ynormalMnyfalse(normalPO4false)3 yE[]normalNa4normalVMnfalse(normalPO4false)3 It is important to mention here that all energies are calculated per formula unit of the species. The trend in the values of formation energies does not follow a typical convex hull in the compositional phase diagram; a break appears at y = 0.50, as indicated by a sharp shoot‐up in the formation energy value (Figure a).…”
Section: Resultsmentioning
confidence: 68%
“…To grasp more insights into these experimental findings, DFT calculations were performed to look at the relative stabilities and the corresponding electronic structures of the Na 3+y V 2−y Mn y (PO 4 ) 3 phases (Figure 5). The relative stabilization energies of the Na 3+y V 2−y Mn y (PO 4 ) 3 systems have been ascertained from their formation energies with respect to varying Mn content (y) and V content (2−y) [42] :…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The second source of dipoles in the polar group of polymer chain makes conformational changes [61]. So, both phenomena together result in the enhancement in the dielectric constant of about ~10 4 and are comparatively higher dielectric constant is observed for SN based SPE (~30×10 4 ) as compared to polymer salts system (~4×10 4 ). Now, after addition of salt in the pure PEO, dielectric constant increases due to the enhancement of the amorphous content.…”
Section: Electrochemical Stability Windowmentioning
confidence: 98%
“…high cost, less abundant and environmental impact. Sodium ion battery (SIB) is an excellent alternative to the LIB and convey subsequent advantages over LIB; (i) Na is highly abundant, (ii) Low cost, and (iii) suitable redox potential (E Na + +Na o = −2.71 V versus standard hydrogen electrode; only 0.3 V above that of lithium) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For the cathodes of Li‐ion batteries, intercalation‐type materials, exhibiting specific capacity about 200 mAh/g, have been widely used for the commercial battery cells . Recent studies showed that transition metal oxides obtained by intercalation can exhibit specific capacities of 100‐150 mAh/g for Na‐ and K‐ion batteries . However, higher‐capacity cathode materials than intercalation‐type materials is desired for the emerging applications, such as EV and ESS.…”
Section: Introductionmentioning
confidence: 99%